Chemical Exposure, Public Health, and Environmental Justice Among Populations Residing Near Industrial Areas: A Literature Review - Aulia Fahira; Fatin Nisrina Athirah (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Industrial chemical exposure has emerged as a critical environmental and public health concern, particularly in Indonesia. Communities residing near industrial zones face heightened risks due to direct and prolonged exposure to hazardous substances. Numerous studies have documented the detrimental health and environmental effects of such exposure, including respiratory illnesses, cancer, and ecological degradation. Socioeconomic disparities further exacerbate these impacts, with marginalized populations often bearing a disproportionate burden of pollution-related consequences. Methods: This study adopts a literature review approach, synthesizing findings from peer-reviewed academic journals, institutional reports, and relevant research to evaluate the health and environmental implications of chemical exposure in industrial areas. Results and Discussion: The review reveals consistent evidence of significant adverse effects stemming from industrial pollution, particularly on vulnerable populations living in proximity to industrial facilities. The compounded risks include both acute and chronic health outcomes and degradation of environmental quality. Conclusion: The implementation of effective mitigation strategies and the enforcement of regulatory policies are essential to reduce chemical exposure risks. Strengthening environmental governance and prioritizing public health in industrial planning are critical steps toward protecting communities in affected areas.